EFEKTIVITAS PENYULUHAN KB IUD TERHADAP TINGKAT PENGETAHUAN PADA PASANGAN USIA SUBUR (PUS) - Is Susiloningtyas; Endang Susilowati; Fitri Nur Shofa (JURNAL MEDIA KESEHATAN, 2022)
Problem: IUD family planning participants have increased in several countries. Nevertheless, there are still IUD KB acceptors who drop out, due to lack of knowledge about IUD KB so that acceptors are afraid to use it. One way that can be done to increase knowledge is by conducting counseling about IUD family planning using audiovisual media or leaflets. The Aim Of The Research: To determine the effectiveness of providing counseling to increase knowledge about IUD family planning in couples of childbearing age. Research Method: National and international literature is searched by means of electronic media using related keywords. The articles used are 5 national articles and 2 international articles. Each article concludes the effectiveness of providing IUD family planning counseling to the level of knowledge of EFA. The Results: counseling is effective in increasing mother's knowledge about IUD family planning. Conclusion: IUD family planning counseling is effective in increasing knowledge about IUD family planning. Keywords: Counseling, Knowledge level, Intra Uterine Device , EFA